Assessment of the Feasibility of Applying the Concept of ‘Controlling’ in the Constitutional Model of Government and Governance of the Republic of Bulgaria - Asenov, Emil (Research Papers, 2021)
The study examines the possibility of applying the concept of “controlling” in the constitutional arrangement and the system of government of the Republic of Bulgaria. The analysis of the existing practices in the management of organisations shows that controlling has been increasingly gaining ground as a leading concept of governance. The proven functional potential of controlling is a prerequisite for its implementation and application in the system of general government. To this end, the study defines a proposal for a change in the functions and powers of the presidential institution in order to exercise supervision and follow-up coordination on the appropriateness and effectiveness of the activities carried out by the executive branch. The proposed constitutional model defines new, broader functions and powers of the presidential institution as an autonomous institution with a non-political character, which must ensure the neutral status and sustainability of the state administration. The new position of the presidential institution in the structure of state authority clearly marks the boundaries and the division between political and non-political power. Its new powers create additional opportunities both for strengthening mutual control and balance between the authorities and for counteracting autocratic tendencies in the state administration